2005
DOI: 10.1021/om050192c
|View full text |Cite
|
Sign up to set email alerts
|

Cycloheptatrienyl−Cyclopentadienyl−Zirconium Sandwich Complexes:  Structure and Bonding

Abstract: The reactions of the 16-electron cycloheptatrienyl−cyclopentadienyl−zirconium sandwich complex [(η7-C7H7)Zr(η5-C5H5)] (1) with tert-butyl isocyanide (tBuNC) and 2,6-dimethylphenyl isocyanide (o-XyNC) have been studied. The isocyanide complexes [(η7-C7H7)(η5-C5H5)Zr(CNR)] (R = tBu, 2a; R = o-Xy, 2b) can be isolated in quantitative yield as stable orange (2a) or red (2b) crystalline solids. The CN stretching vibrations are observed at 2156 (2a) and 2134 cm-1 (2b) in KBr, indicating a relatively weak zirconium−is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
60
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 58 publications
(64 reference statements)
11
60
0
Order By: Relevance
“…[40] Furthermore, we have used the symmetric complex 2 as a representative example to identify pertinent frontier molecular orbitals; Figure 3 shows the contour plots of the LUMO and the seven HOMOs based on the M05-2X calculation. Similarly to the bonding in trozircene [19] and halfopen trozircenes,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[40] Furthermore, we have used the symmetric complex 2 as a representative example to identify pertinent frontier molecular orbitals; Figure 3 shows the contour plots of the LUMO and the seven HOMOs based on the M05-2X calculation. Similarly to the bonding in trozircene [19] and halfopen trozircenes,…”
Section: Resultsmentioning
confidence: 99%
“…Our group has especially focused on Group 4 Cht-Cp sandwich complexes, [18] in which-based on experimental and theoretical results-a formal + 4 oxidation state can be assigned to the metal atom, implying that the C 7 H 7 ligand is best considered as a trianion. [19,20] Consequently, the metal atom in these 16-electron complexes is Lewis acidic, and thus able to coordinate additional two- (4). The presence of Lewis basic phosphorus atoms and Lewis acidic zirconium atoms allows ambiphilic behaviour to be observed, and X-ray diffraction analysis reveals dimeric arrangements for 2 and 3 with long intermolecular ZrÀP bonds, whereas 4 remains monomeric in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For M = Ti, we were able to demonstrate that the introduction of a silylene bridge makes the coordinating rings significantly non-parallel and opens a potential vacancy at the titanium centre; thus adducts with carbon monoxide and isocyanides have been observed [5a], whereas the parent 16-electron complex [(g 7 -C 7 H 7 )Ti(g 5 -C 5 H 5 )] (troticene) does not form adducts with simple two-electron ligands. In contrast, the corresponding zirconium complex [(g 7 -C 7 H 7 )Zr(g 5 -C 5 H 5 )] (trozircene, 1a) has been shown to react with isocyanides [8], phosphines and N-heterocyclic carbenes [9] without the need to resort to the introduction of a bridging unit (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, early work by Wilkinson and co-workers [17] suggested that reactions of tropylium salts with transitionmetal derivatives were rarely suitable for the preparation of η 7 -C 7 H 7 metal complexes. More recent studies on η 7 -C 7 H 7 -metal complexes suggest preferred formulations of such complexes as derivatives of the 10 π-electron trianion [18][19][20][21] C 7 H 7 3-, which has been generated in a metal-free form by the treatment of 1,4-cycloheptadiene with nBuLi. [22,23] Thus the metal formal oxidation states in the known mixed sandwich complexes (η 5 -C 5 H 5 )M(η 7 -C 7 H 7 ) (M = Ti, V, Cr) may be considered to be +4 in contrast to the formal zero metal oxidation states in the isoelectronic and isomeric dibenzenemetal complexes (η 6 -C 6 H 6 ) 2 M (M = Ti, V, Cr).…”
Section: Introductionmentioning
confidence: 99%